Fix it in post : solutions for postproduction problems - James, Jack, 1977- (Amsterdam ; Focal Press, 2009)
This book provides an array of concise solutions to the wide variety of problems that are faced by postproduction artists in the post process. With an application-agnostic approach, it gives proven, step-by-step methods to solving the most frequently encountered postproduction problems. Solutions are provided for common audio, video, digital, editorial, color, timing and compositing problems.--From publisher description.
Includes index.
Keywords: Motion pictures -- Editing -- Data processing; Video tapes -- Editing -- Data processing